2015
DOI: 10.48550/arxiv.1505.05500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The i-process and CEMP-r/s stars

Abstract: We investigate whether the anomalous elemental abundance patterns in some of the C-enhanced metal-poor-r/s (CEMP-r/s) stars are consistent with predictions of nucleosynthesis yields from the i-process, a neutron-capture regime at neutron densities intermediate between those typical for the slow (s) and rapid (r) processes. Conditions necessary for the i-process are expected to be met at multiple stellar sites, such as the He-core and He-shell flashes in low-metallicity low-mass stars, super-AGB and post-AGB st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Instead, given these stars' resemblance to s-process-enhanced stars with large carbon abundances, recent theoretical research has begun to suggest that a neutron source intermediate between the s-and r-processes might be operating, and responsible for these observed chemical signatures. This led to the (re)introduction of the so-called intermediate neutron-capture process, or i-process (Dardelet et al 2015;Hampel et al 2016), following an original suggestion by Cowan & Rose (1977). This process supposedly operates under neutron densities of nn ≈ 10 15 cm −3 , several orders of magnitude higher than what is required for the s-process (nn ∼ 10 8 cm −3 ; see Section 3.1), but likely varying neutron exposures (Dardelet et al 2015).…”
Section: The Astrophysical Signature Of the I-processmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, given these stars' resemblance to s-process-enhanced stars with large carbon abundances, recent theoretical research has begun to suggest that a neutron source intermediate between the s-and r-processes might be operating, and responsible for these observed chemical signatures. This led to the (re)introduction of the so-called intermediate neutron-capture process, or i-process (Dardelet et al 2015;Hampel et al 2016), following an original suggestion by Cowan & Rose (1977). This process supposedly operates under neutron densities of nn ≈ 10 15 cm −3 , several orders of magnitude higher than what is required for the s-process (nn ∼ 10 8 cm −3 ; see Section 3.1), but likely varying neutron exposures (Dardelet et al 2015).…”
Section: The Astrophysical Signature Of the I-processmentioning
confidence: 99%
“…This led to the (re)introduction of the so-called intermediate neutron-capture process, or i-process (Dardelet et al 2015;Hampel et al 2016), following an original suggestion by Cowan & Rose (1977). This process supposedly operates under neutron densities of nn ≈ 10 15 cm −3 , several orders of magnitude higher than what is required for the s-process (nn ∼ 10 8 cm −3 ; see Section 3.1), but likely varying neutron exposures (Dardelet et al 2015). Invoking a large neutron exposure (Busso, Gallino & Wasserburg 1999) results in an increased production of heavy neutron-capture elements at and the second peak (roughly 55 < Z < 75), as is needed to match the observations.…”
Section: The Astrophysical Signature Of the I-processmentioning
confidence: 99%
“…Heavy elements (with atomic numbers Z > 30) are dominantly produced in the slow (s) and rapid (r) neutron-capture process. The intermediate (i) process (e.g., Dardelet et al 2015;Hampel et al 2016Hampel et al , 2019Koch et al 2019;) and the light element primary process (LEPP, e.g., Travaglio et al 2004;Montes et al 2007) may also contribute to the enrichment of heavy elements. Both, the s-and the r-process, are hosted by distinct astrophysical production sites and carry individual chemical fingerprints (for reviews of the r-process and the origin of heavy elements see, e.g., Cowan et al 1991;Sneden et al 2008;Thielemann et al 2011Thielemann et al , 2017Frebel 2018;Horowitz et al 2019;Cowan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The CEMP-s stars (high Ba), have proven to be mostly in binary systems, and it is generally accepted that the overabundance of C and the heavier elements in most of these stars is caused by accretion from a companion AGB star (Lucatello et al 2005;Starkenburg et al 2014;Abate et al 2015bAbate et al ,a, 2018Hansen et al 2016b), while some might show the nucleosynthetic products of spinstars, for instance, rapidly rotating (single) massive stars (Choplin et al 2017). Similarly, it has been suggested that the CEMP-i stars (enhanced in both Ba and Eu; also known as CEMP-r/s stars) are the result of a mass transfer from a binary companion that has undergone the i-process (Lugaro et al 2009;Campbell et al 2010;Dardelet et al 2015;Hampel et al 2016;Koch et al 2019). The CEMP-r (high Eu) stars are believed to be polluted in heavy elements mainly by one source (Frebel 2018).…”
Section: Carbon-enhanced Metal-poor Starsmentioning
confidence: 99%